Modeling of the relationship among organizational justice, organizational indifference and organizational commitment in faculty members of Kurdistan University of Medical Sciences - Zahed Rezaei (Zanjan University of Medical Sciences and Health Services, 2020)
Abstract Background & Aim: Today, organizations need employees who are committed to organizational goals, avoid any form of indifference toward the organization, and extend efforts to realize these goals in order to survive. The present study aimed to evaluate the mediating role of organizational indifference in the relationship between organizational justice and organizational commitment in professors of Kurdistan University of Medical Sciences. Materials and Methods: This descriptive-correlational study was performed on all professors in Kurdistan University of Medical Sciences (n=235) in 2017. In total, 147 subjects were selected based on the Morgan table. Data were collected using the organizational justice scale is Niehoff and Moorman, organizational commitment questionnaire by Allen and Meyer, and organizational indifference questionnaire by Danaeifard et al. Moreover, data analysis was performed in SPSS version 21 using descriptive (mean and standard deviation) and inferential (Pearson's correlation coefficient and Kolmogorov-Smirnov test) statistics. Furthermore, the structural equation method (SEM) was applied in LISREL software. Results: In this study, organizational justice had a direct and positive effect on organizational commitment, whereas organizational indifference had a direct and negative impact on organizational commitment. Moreover, organizational justice had a direct and negative effect on organizational indifference while organizational commitment had an indirect significant impact on organizational commitment through organizational indifference. Conclusion: Given the fact that organizational commitment and organizational indifference are important variables related to professors' organizational commitment, it is suggested that the two variables be considered by university managers.